Country and Gender Differences in the Functioning of CEFR-Based Can-Do Statements as a Tool for Self-Assessing English Proficiency. Issue 3 (2nd July 2016) - Denies, Katrijn; Janssen, Rianne
ABSTRACT: This study discusses the self-assessments of over 22, 500 students on a set of 12 can-do statements that are taken from the Common European Framework of Reference (CEFR). The students' endorsement or negation of the statements reflects their sense of self-efficacy in English reading, writing, and listening. Their self-efficacy beliefs are compared to their proficiency level as measured in the European Survey on Language Competences. As expected, four-level mixed-effects logistic regression analyses show positive correlations between proficiency and the probability of endorsing the can-do statements. However, patterns in this relationship are influenced by the students' gender and country. As such, the study shows how far the understanding of 15-year-olds' own skills can vary across countries and between boys and girls, even when the skill descriptions that the students are offered rely on the highly concrete "common language" that is provided by the CEFR.